Development Of A Product Green Functional Assessment Tool To Improve Resources Sustainability - Fu Haw, Ho; Jun Xin, See Toh (Research Progress in Mechanical and Manufacturing Engineering, 2021)
The fast growing of industrialization has leads to drastic growth of packaging waste issue, e.g. packaging waste from global e-commerce trading. Although every product requires basic packaging before it could be shipped to the customer, but most of the time the packaging materials will end up turn into solid waste or pollutants. For that reason, the demand for green packaging research is tremendously needed, but it is still considerable limited in current studies. In this study, the aims is to understand the criteria of green packaging, next , develop an assessment tool to evaluate the packaging  in term of green criteria. The methodology used in this study is extracting the criteria and sub-criteria from existing journal or books. In second stage of the study, AHP approach was chosen for data collection and data analysis particularly on the green criteria performance weightage. From the research results, there are 3 green packaging criteria were assessed, the priority orders of these criteria are the material of green packaging, design of the green packaging and followed by the process used to produce the packaging. The assessment tool then were validate by two experts which majored in eco design, product design and sustainable manufacturing from Universiti Teknikal Malaysia Melaka (UTeM) and University Nottingham Malaysia. With the development of green packaging tool, perhaps it could provide a quick assessment on packaging especially on the green aspects.